Again and again: exploring the influence of disclosure repetition on children's cognitive processing of product placement. Issue 5 (3rd July 2020) - Spielvogel, Ines; Naderer, Brigitte; Matthes, Jörg
Abstract: In order to help viewers recognize the persuasive attempts of product placement (PP), broadcasters are obligated to present disclosures and, in most countries, those disclosures must be presented repeatedly. The repeated inclusion of disclosures is especially important when it comes to children who are less equipped to detect persuasive messages compared to adults. To date, however, the role of disclosure repetition for children's cognitive processing is unclear. Hence, we conducted an eye-tracking study with 105 children to shed light on the effect of disclosure repetition on children's implicit cognitive processing of PP (i.e., attention toward the placement). Results demonstrated that disclosure repetition led to less attention toward the subsequently presented embedded brand compared to no and a one-time disclosure. Additionally, more attention triggered the explicit activation of persuasion knowledge. Age did not moderate this effect. Overall, the findings underline the importance of disclosure repetition to shield children against persuasive influence.